Community Intentions In Non-Cash Payments - Uswatun Khasanah, Aulia; Wisnu Utomo, Chandra; Erikawati, Civi; Danuri, Azis; Aulia Insani, Kharisma (BALANCE: Economic, Business, Management and Accounting Journal, 2024)
Bank Indonesia has launched the National Cashless Movement (GNNT). In practice, non-cash transactions cannot be applied optimally in society. Various factors influence the intention to use non-cash payments in society. This research aims to determine the intention to use non-cash payments as a means of payment. This research uses data collection techniques in the form of surveys by distributing questionnaires online. The respondents of this research were 164 e-money users from various regions in Indonesia. The Unified Theory of Acceptance and Use of Technology (UTAUT2) is the approach taken. This research uses the PLS-SEM model. The research results show that hedonic motivation is vital in encouraging people to make non-cash payments.